2020
DOI: 10.1097/pai.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell Nuclear Differentiation Antigen (MNDA) Positivity in Primary Follicles: Potential Pitfall in the Differential Diagnosis With Marginal Zone Lymphoma

Abstract: Myeloid cell nuclear differentiation antigen (MNDA) is an immunohistochemical marker that is used to distinguish marginal zone lymphomas (MZLs) from other small B-cell lymphomas. An index case that showed MNDA staining in primary follicles prompted the current study to evaluate whether MNDA expression is widespread in primary follicles and to address whether it poses a potential diagnostic pitfall. Of the 15 cases with primary follicles identified by a search of the laboratory information system, 7 had positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Another point of consideration for MNDA is its weak nuclear expression on the naive B-cells of the primary follicles. This should be kept in mind especially while evaluating small biopsies [ 28 ]. Another important finding of our study is the significant expression of MNDA in CLL samples (p=0.019).…”
Section: Discussionmentioning
confidence: 99%
“…Another point of consideration for MNDA is its weak nuclear expression on the naive B-cells of the primary follicles. This should be kept in mind especially while evaluating small biopsies [ 28 ]. Another important finding of our study is the significant expression of MNDA in CLL samples (p=0.019).…”
Section: Discussionmentioning
confidence: 99%
“…MNDA expression in the primary follicle was previously reported as potential pitfall in the differential diagnosis with MZL. 14 We observed that in primary follicular hyperplasia, MNDA expression was confined to follicles, while MNDA-positive cells always showed infiltrative pattern involving interfollicular areas, germinal centers in SBCLs. Based on our experiences, these expression patterns are very useful in differentiating primary follicle from SBCL, especially when combined with other markers such as LEF-1, cyclin D1, BCL-6.…”
Section: Discussionmentioning
confidence: 64%
“…MNDA and PDIA6 were 2 of the upregulated proteins ( Table 1 ). The MNDA protein is a salivary biological marker for Sjogren Syndrome and for distinguishing between different kinds of lymphomas ( 80 , 81 ). MNDA is also related to NF-kappa-B, apoptosis and autophagy signaling pathways.…”
Section: Discussionmentioning
confidence: 99%